Design and fabrication of 3D printed universal gripper - Lee, Gerwyn Si Yan (Nanyang Technological University, 2022)
The Gripper Mechanism has existed since ancient times and was automated in 1969. As technology advances, human labour becomes less of a demand and were replaced by autonomous grippers. Despite having an abundance of grippers, most available designs are too rigid and not adaptable to various shapes and sizes, limiting their applications. The exerted force is unsuitable for soft objects as well, bruising them in the process of gripping. Considering the crops and fruits within the farm, the gripper must be able to hold soft objects without damaging them while being adaptable to a myriad of shapes and sizes. Hence, this study aims to investigate the following factors: the force limitations of both the crops and the grippers, and nature-inspired designs for adaptiveness and to maximise efficiency. This report illustrates the designs and experiments for a 3D Printed Universal Gripper. Thermoplastic Polyurethane (TPU) 95A of various densities underwent Tensile Stress Test to obtain the required data. Stress Analyses were carried out via Autodesk Inventor using gathered data to determine viable density for printed fingers. Shape-memory Alloy (SMA), both Ni-Ti and Ni-Ti-Cu, of 0.5mm diameter will be used to actuate the gripper. The SMAs underwent Shape Characterisation via heat treatment to determine their characterised position.